Exercise and Physical Activity Counseling Needs among Cardiac Rehabilitation Patients (Unnes Journal of Public Health, 2021)
Cardiac rehabilitation (CR) has decreased in recurrent cardiac events. However, information related the needs of cardiac rehabilitation patients such as exercise and physical activities counseling are very limited. This study aims to identify the needs of cardiac rehabilitation patients such as exercise, physical activity counselling, and the relationship between them. It also applied a quantitative approach combined with a descriptive correlational method. 38 cardiac rehabilitation patients were recruited as samples and were selected using the convenience sampling technique. Data collection was performed using questionnaires filled out by the respondents (with a retrospective technique) at the end of the CR program, and the results were evaluated through descriptive correlational statistics. The results revealed that patients with CR required exercise (92.1%) and nurses' counseling for physical activities (86.9%). It also indicates that there is a statistically positive relationship between exercise and physical activities counseling among CR patients (r = 0.485, p < 0.01). Consequently, most CR patients desire nurses to take part in their exercise and physical activities. The needs of CR patients on exercise and physical activity counseling were correlated positively. Therefore, information regarding exercise and physical activity for CR patients should be provided simultaneously to complement each other.